Item generation for test development - Irvine, S. H.; Kyllonen, Patrick C. (Lawrence Erlbaum Associates, 2002)
This work covers topics such as: the psychometric and cognitive theory of item generation; construct-oriented approaches to item generation; implementation; and applications of item-generative principles.